Hal-Hal Yang Ada Hubungan Dengan Penyakit Jantung Koroner Pada Penderita Di Beberapa Lokasi Wilayah Indonesia Periode Tahun 2010 Sampai Dengan Tahun 2021 - Kamsa, Khairu Nisa; Selomo, Makmur; Rahmadani, Andi Annisa (Fakultas Kedokteran Universitas Bosowa, 2024)
Coronary heart disease is a condition of insufficient supply of blood and oxygen to the heart muscle. The most common cause of myocardial ischemia is atherosclerotic disease in one or more of the epicardial coronary arteries that is severe enough to cause inadequate blood flow and perfusion to the heart muscle supplied by the coronary arteries. The purpose of this study is to find out things that have to do with coronary heart disease in several regions of Indonesia for the period 2010 to 2021. This research method is an analytical research by synthesizing the results obtained from fourteen scientific research journals with a case control research design. The results of the research from fourteen journals analyzed showed that there were things that were related to coronary heart disease in several locations in Indonesia, namely there was a significant relationship between Diabetes Mellitus, obesity, smoking, hypertension, dyslipidemia, fa mily history of coronary heart disease with hypertension. values <0.05. The conclusion of coronary heart disease in several locations in the territory of Indonesia for the period 2010 to 2021 there is a significant relationship with diabetes mellitus, obesity, smoking, hypertension, dyslipidemia, family history.